Embedding Pinhole Vertical Gold Nanowire Electronic Skins for Braille Recognition. Issue 13 (28th February 2019) - Ling, Yunzhi; Gong, Shu; Zhai, Qingfeng; Wang, Yan; Zhao, Yunmeng; Yang, Mingjie; Cheng, Wenlong
Abstract: Electronic skins (e‐skins) have the potential to be conformally integrated with human body to revolutionize wearable electronics for a myriad of technical applications including healthcare, soft robotics, and the internet of things, to name a few. One of the challenges preventing the current proof of concept translating to real‐world applications is the device durability, in which the strong adhesion between active materials and elastomeric substrate or human skin is required. Here, a new strategy is reported to embed vertically aligned standing gold nanowires (v‐AuNWs) into polydimethylsiloxane, leading to a robust e‐skin sensor. It is found that v‐AuNWs with pinholes can have an adhesion energy 18‐fold greater than that for pinhole‐free v‐AuNWs. Finite element modeling results show that this is due to friction force from interfacial embedment. Furthermore, it is demonstrated that the robust e‐skin sensor can be used for braille recognition. Abstract : Vertically aligned standing gold nanowires with pinhole structure can be embedded into a polydimethylsiloxane elastomeric substrate, leading to a robust electronic skin. The conductivity of the as‐obtained electronic skin is sensitive to shear force‐induced localized deformation, indicating potential applications in the use of braille alphabets.